A steganography application for secure data communication - Baykara, Muhammet; Das, Resul (IEEE Computer Society, 2013)
Information security is the process of protecting information and information systems from unauthorized access, use, disclosure, disruption, modification or destruction. Nowadays, apart from the military and institutional information security, individual information security is very important. If individual information security is ignored, it can cause intangible damage and monetary loss. In this study, a steganography application was developed to increase personal information security. This application is intended to provide a more secure way of communication for emails which play an important role in personal data transfer. Thus, Steganography, which is one of the communication hiding techniques, is used. And also existing steganography methods are examined and a new application has been developed to be used for personal information security. Finally, this application was applied to an electronic mail communication. © 2013 IEEE.
2013 10th International Conference on Electronics, Computer and Computation, ICECCO 2013 -- 7 November 2013 through 8 November 2013 -- Ankara -- 102696
Keywords: Computer security; Information hiding; Information security; LSB; Steganography